Characterization of a pathway−specific activator of edeine biosynthesis and improved edeine production by its overexpression in Brevibacillus brevis - Du, Jie; Zhang, Cuiyang; Long, Qingshan; Zhang, Liang; Chen, Wu; Liu, Qingshu (Frontiers in Plant Science, 2022)
Edeines are a group of non-ribosomal antibacterial peptides produced by Brevibacillus brevis. Due to the significant antibacterial properties of edeines, increasing edeine yield is of great interest in biomedical research. Herein, we identiﬁed that EdeB, a member of the ParB protein family, significantly improved edeine production in B. brevis. First, overexpression of edeB in B. brevis X23 increased edeine production by 92.27 %. Second, in vitro bacteriostasis experiment showed that edeB-deletion mutant exhibited less antibacterial activity. Third, RT-qPCR assay demonstrated that the expression of edeA, edeQ, and edeK, which are key components of the edeine biosynthesis pathway, in edeB-deletion mutant X23(ΔedeB) was significantly lower than that in wild-type B. brevis strain X23. Finally, electrophoretic mobility shift assay (EMSA) showed that EdeB directly bound to the promoter region of the edeine biosynthetic gene cluster (ede BGC), suggesting that EdeB improves edeine production through interaction with ede BGC in B. brevis.